Early versus Delayed Internal Urethrotomy for Recurrent Urethral Stricture after Urethroplasty in Children - Hosseini, Seyyed Yousef; Safarinejad, Mohammad Reza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Our aim was to evaluate the results of early versus delayed internal urethrotomy for management of recurrent urethral strictures after posterior urethroplasty in children. Materials and Methods: Twenty boys with proven posterior urethral strictures were treated by perineal posterior urethroplasty. Of these, 12 required internal urethrotomy. Each radiograph demonstrated a patent but irregular urethra with a decrease in diameter at the point of repair (fair results). Patients were then divided into 2 groups: 6 underwent early (within 6 weeks from urethroplasty), and 6 underwent delayed (after 12 weeks from urethroplasty), internal urethrotomy with the cold knife as a complementary treatment. The groups were comparable in terms of patient age, etiology of the primary urethral stricture, number of recurrences, length and site of the actual stricture, and preoperative maximum flow rate. Mean follow-up was 5 years. Results: Kaplan-Meier analyses showed that the stricture-free rate was 66.6% after early, and 33.3% after delayed, internal urethrotomy (P = .03). Conclusion: Early internal urethrotomy should be considered in boys with recurrent urethral stricture after urethroplasty.